AI-Driven Cloud Transformation for Product Management: Optimizing Resource Allocation, Cost Management, and Market Adaptation in Digital Products (Internet of Things and Edge Computing Journal, 2022)
The advent of artificial intelligence (AI) has catalyzed a transformative shift in the paradigms of product management, particularly within the context of cloud-based platforms. This research paper explores the integration of AI in cloud transformation, elucidating its potential to optimize resource allocation, enhance cost management, and facilitate market adaptation for digital products. The study posits that AI-driven methodologies not only streamline operational efficiencies but also augment strategic decision-making processes, thereby enabling organizations to remain competitive in an increasingly volatile market landscape.Resource allocation has traditionally been constrained by human-centric limitations, often leading to suboptimal utilization of available assets. However, AI technologies, such as machine learning and predictive analytics, can dynamically assess resource requirements and adjust allocations in real time. This capability is particularly vital for organizations operating in cloud environments, where elasticity and scalability are paramount. By employing advanced algorithms, businesses can analyze vast datasets to identify patterns and forecast demand, ultimately ensuring that resources are aligned with strategic objectives.In the domain of cost management, AI serves as a pivotal tool for mitigating expenditures associated with digital product lifecycle management. Through the application of AI-powered analytics, organizations can identify inefficiencies in their processes and operational workflows, thereby minimizing waste and enhancing overall productivity. Moreover, AI facilitates intelligent budgeting practices by enabling real-time financial monitoring and predictive modeling, allowing companies to make informed financial decisions that align with their long-term strategic goals.